Решите уравнение: (x^2-4x+6)^2 - 4(x^2-4x+6)+6=x

Решите уравнение: (x^2-4x+6)^2 - 4(x^2-4x+6)+6=x
Гость
Ответ(ы) на вопрос:
Гость
(x^2-4x+6)^2 - 4(x^2-4x+6)+6=x (x^4-8x^3+28x^2-48x+36)-(4x^2-16x+24)+6=x x^4-8x^3+24x^2-33x+18=0 (x^4-33x+18)+(-8x^3+24x^2)=0 (x^3+3x^2+9x-6)(x-3)+(-8x^2)(x-3)=0 (x^3+3x^2-8x^2+9x-6)(x-3)=0 1)  x^3+3x^2-8x^2+9x-6=0      (x^3-2x^2)-(3x^2-6x)+(3x-6)=0      x^2(x-2)-3x(x-2)+3(x-2)=0      (x^2-3x+3)(x-2)=0       a)  x^2-3x+3=0            D=b^2-4ac=-3 - нет решений       б)  x-2=0 =>x=2 2) x-3=0 => x=3 ответ: x=2;  x=3 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы